Pengambilan Keputusan Pembelian Produk Hasil Kewirausahaan Mahasiswa Program Studi Manajemen Pemasaran Warga Negara Berkebutuhan Khusus di Lingkungan Politeknik Negeri Jakarta - Rovino Katuruni, Innas; Nur Praptiwi, Rahma; Lukitaningrum, Kristin (Syntax Literate, 2025)
The Marketing Management Study Program for Citizens with Special Needs (MP-WNBK) at Politeknik Negeri Jakarta (PNJ) facilitates individuals with disabilities in obtaining vocational education at the diploma level. The current students of the MP-WNBK Study Program at PNJ consist of 70 active students with various disabilities, including hearing impairments (deaf), physical disabilities, Down syndrome, slow learners, Autism Spectrum Disorder (ASD), and Attention Deficit Hyperactivity Disorder (ADHD). One of the courses in the curriculum of MP-WNBK PNJ is the sales course in the 3rd semester, and Entrepreneurship 1 and 2 courses in the 5th and 6th semesters. In these three courses, students are encouraged to directly engage in business activities and have specific sales targets. Some students were able to generate profits exceeding IDR 2,000,000 in two months. This data sparked the author's curiosity to explore the decision-making process of buyers of products from MP-WNBK PNJ students. The data collection for this research was conducted from April to August 2024, located at the PNJ campus. This study used a survey method with a Likert-scale questionnaire. The sample size was 65 respondents, determined through purposive sampling. The research was conducted using a quantitative descriptive method. The conclusion of this study is that the reasons respondents purchased the products included attractive product appearance, recommendations from others, and immediate need. Support from the surrounding environment is strongly believed to be a major factor in their financial independence. Feedback from respondents for future product improvements includes enhancing promotions, increasing product variety, and improving labels and packaging to make them more appealing.